The EU Migration Partnership Framework: time for a rethink? - Clare Castillejo (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The European Union's (EU) Migration Partnership Framework (MPF) was established in June 2016 and seeks to mobilise the instruments, resources and influence of both the EU and member states to establish cooperation with partner countries in order to “sustainably manage migration flows” (European Commission, 2017a, p. 2). Its strong focus on EU interests and positive and negative incentives mark a departure from previous EU migration initiatives and have generated significant controversy. This Discussion Paper examines the politics, implementation and impact of the MPF more than one year on from its establishment, asking what lessons it offers for the future direction of EU migration policy. The paper begins by introducing the MPF and examining the different perspectives of EU actors on the framework. It finds that there is significant disagreement both among EU member states and within EU institutions over the MPF's approach and priorities. The paper explores the political and ethical controversies that the MPF has generated, including regarding its ambition to subordinate other areas of external action to migration goals; its use of incentives; and its undermining of EU development and human rights principles. The paper assesses the implementation and impact of the MPF in its five priority countries – Ethiopia, Mali, Niger, Nigeria and Senegal. It argues that the concrete achievements of the migration partnerships have been limited; that the MPF has largely failed to incentivise the cooperation that the EU was seeking; and that the EU's migration programming in MPF partner countries has suffered from serious flaws. The paper takes an in-depth look at the Ethiopia partnership, which has been the most challenging. It describes how the interests and goals of the EU and Ethiopia have not aligned themselves, how the issue of returns has come to entirely overshadow engagement, and how the relationship between the partners has been soured. The paper goes on to examine how the MPF relates to African interests and how it has affected EU-Africa relations, arguing that the MPF approach is seen by many African actors as imposing EU interests and undermining African unity and continental ambitions. Finally, it explores how the EU can develop engagement with Africa on migration issues that is more realistic, constructive, and sustainable, with the aim of fostering intra-African movement and economic opportunities; ensuring protection for refugees and vulnerable migrants; and allowing both continents to benefit from large-scale, safe and orderly African labour migration to Europe. However, it warns that any such shift will require a change in mindset by European leaders and populations.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Flucht und Migration